Biotin interference with laboratory test results - Strilić David Z.; Stanimirov Bojan G.; Đanić Maja P. (Hospital Pharmacology)
Introduction: Biotin interference in laboratory tests is a growing concern, particularly due to the widespread use of biotin not only as a therapeutic agent but also as a supplement in the cosmetic industry. Immunoassays utilizing biotin-streptavidin technology are especially susceptible to interference, which can result in inaccurate test results, misdiagnosis, and inappropriate treatment. Methodology: This review synthesizes information from scientific literature available through databases like PubMed and Google Scholar. Keywords such as "biotin", "interference" and "immunoassay" were used to identify relevant studies. Topic: This review addresses the risk of biotin interference in various immunoassays, particularly its impact on thyroid function tests (TSH, FT3, FT4), parathyroid hormone (PTH), testosterone, human chorionic gonadotropin (hCG), and cardiac markers including troponin. It explores the pharmacokinetics of biotin elimination and the prevalence of elevated biotin levels in patient populations. The clinical consequences of falsely high or low results , potentially leading to misdiagnosis, are highlighted. Methods for mitigating biotin interference , such as serial dilution, biotin depletion, and advancements in biotin-resistant immunoassays, are also discussed. Conclusion: Biotin interference presents a significant challenge in laboratory diagnostics, particularly with the growing use of high-dose biotin supplements. Tests most susceptible include those assessing thyroid function, reproductive hormones, and cardiac markers. Raising awareness among healthcare professionals and patients, along with implementing biotin depletion protocols and improving immunoassay designs, are key strategies to mitigate interference. Continued research into biotin-resistant immunoassays is critical for enhancing diagnostic accuracy and preventing clinical misinterpretation.